PENDIDIKAN ISLAM BERBASIS TAUHID PADA KISAH NABI IBRAHIM PADA AL-QUR’AN SURAH AL-‘AN’AM AYAT 74-79 - Hamiyah Zuleika Alifah, Tomi Prandana, Cahaya, Siti Hawa Lubis, (Program Studi Pendidikan Islam Pascasarjana UIN Sumatera Utara Medan, 2023)
Abstract: In the Qur'an many are listed about ibrah or lessons that call for monotheism and the faith of a Muslim since the care of the prophet Adam AS to the prophet Muhammad SAW. One of the ibrah that we can take is from the story of Prophet Ibrahim AS listed in the Qur'an surah Al an,am 74-83 which explains the education and story of Prophet Ibrahim which calls on the monotheism of Prophet Ibrahim AS. Rubūbiyah monotheism education contained in verse 75 which explains that Allah SWT has shown signs of the greatness of Allah SWT in the sky and on earth to the prophet Ibrahim as so that his soul is directed Uluhiyah monotheism education This uluhiyah monotheism education is contained in verse 74 which explains that the father and the people of the prophet Ibrahim as making the idols they made as god. And verse 79, namely, the sincerity of Prophet Ibrahim as to surrender his gaze to Allah SWT and not follow his people to associate with Allah by worshiping other than Him such as worshiping the stars, the moon and the idols they made.Keywords : Monotheism Education; Surat Al- An’am; Islamic Education.